Is there a place for environmental education in religious education in Türkiye? - Kurttekin, Fatma (Journal of beliefs and values, 2026)
The study aims to assess the integration of environmental education within religious education in Türkiye. Employing a qualitative research approach, the analysis focuses on aspects like the physical environment, environmental degradation, and associated issues. The investigation found that the curricula and Religious Culture and Moral Knowledge textbooks explicitly address environmental concerns at the 4th and 10th-grade levels. However, the treatment of the environmental concept needs a comprehensive and structured approach. The study’s results indicate that environmental education is partially integrated into religious education, viewed as a component of one’s religious obligations and a means to demonstrate devotion to Allah. These conclusions are drawn from a set of guiding principles and religious, ethical considerations.